PERANCANGAN BUSINESS MODEL CANVAS (BMC) UNTUK MENINGKATKAN PENJUALAN PADA TOKO LAVA COLLECTION DI KECAMATAN BULULAWANG KABUPATEN MALANG - Aisah Aulia Fajria; Ayu Sulasari; Rizky Kurniawan Murtiyanto (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
In the current era of globalization and digital transformation, business competition is becoming increasingly intense. Lava Collection Store, located in Bululawang District, faces significant challenges, particularly a notable decline in sales. This decline is driven by changes in consumer behavior, with a growing preference for the convenience of online shopping, limited utilization of digital technology in marketing and business operations, and a lack of innovative marketing strategies. This study aimed to identify the problems faced by Lava Collection in designing a business model using the Business Model Canvas (BMC) approach, and implementing digital marketing strategies to increase sales, particularly through the Shopee e-commerce platform. The research used a descriptive method with a qualitative approach by collecting data through in-depth interviews with various relevant parties. The results showed that the main weakness of Lava Collection lies in the Channels element, which has not been utilized optimally. The design and implementation of the BMC which emphasized the strengthening of digital distribution Channels, had driven the business toward positive development. The implementation of digital marketing strategies through Shopee has proven to enhance the product visibility, increase consumer interaction, and generate new sales transactions that support the sustainability of the business in the digital era..